Оцінка евклідових параметрів суміші двох симетричних розподілів - Майборода, Р.Є.; Сугакова, О.В. (Український математичний журнал, 2010)
Наблюдается выборка со смеси двух симметричных распределений, отличающихся только смещением. Построены оценки метода оценивающих уравнений параметров средних положений и концентраций (вероятностей смешивания) обеих компонент. Получены условия асимптотической нормальности этих оценок. Найдена точная нижняя грань для коэффициентов рассеяния оценок. A sample from a mixture of two symmetric distributions is observed. The considered distributions differ only by a shift. Estimates are constructed by the method of estimating equations for parameters of mean locations and concentrations (mixing probabilities) of both components. We obtain conditions for the asymptotic normality of these estimates. The greatest lower bounds for the coefficients of dispersion of the estimates are determined.